POSSIBILITIES OF MINIMALLY INVASIVE INTERVENTIONS IN THE TREATMENT OF LIVER ABSCESSES (The New Uzbekistan Journal of Medicine, 2025)
The presented work analyzes the results of treatment of 168 patients with liver abscesses, who were on inpatient treatment in the multidisciplinary clinic of TMA, for the period from 2015 - 2022. The main instrumental methods of investigation are: Ultrasound and multispiral computed tomography. To date, minimally invasive interventions are highly effective, provided adequate local sanitation and targeted antibiotic therapy. These operations should be performed in specialized institutions and by high-level specialists, as multiple punctures with attempted catheterization lead to traumatization, with the development of complications.  The recommended tactics of patient management allows to control the inflammatory process, with adequate cleansing of the abscess cavity. Inclusion of VVACP in the complex of treatment measures at the stage of infiltration allows to prevent abscess formation.